SOCIAL CONSTRUCTION OF SOCIAL SCIENCE TEACHERS REGARDING SOCIAL SCIENCE LEARNING IN THE “MERDEKA CURRICULUM” - Hadi Wiyono (Jurnal Scientia, 2023)
This research aims to determine the social construction of social studies teachers regarding Merdeka Curriculum Social Studies Learning in Pontianak City and Singkawang City and to find out the factors that influence the social construction of Merdeka Curriculum Social Studies Learning by Social Sciences Teachers in Pontianak City and Singkawang City. The method used in this research uses qualitative research methods in the form of descriptive qualitative research. The data sources in this research are social studies teachers in Pontianak City and Singkawang City who implement the Merdeka Curriculum. Data collection techniques use observation, interviews and documentation techniques. This research involved 10 teachers consisting of 5 social studies teachers at junior high school level in Singkawang City and 5 social studies teachers in Pontianak City. Data collection tools use observation guidelines, interview guidelines, and cellphone cameras. The data analysis technique uses the interactive analysis technique of the Miles and Huberman model which consists of data reduction, data presentation and drawing conclusions. The results of the research reveal that the social construction of social studies teachers regarding Merdeka Curriculum Social Studies Learning in Pontianak City and Singkawang City varies. There are two categories regarding how social studies teachers construct social studies learning in the Merdeka Curriculum, including social studies learning in the Merdeka curriculum which is interpreted as appropriate or not according to the competencies and conditions of students. Factors that influence the social construction of Merdeka curriculum social studies learning by social studies teachers in Pontianak City and Singkawang City include teacher age, student conditions, Merdeka curriculum webinars, the role of driving teachers, and school infrastructure.